2005
DOI: 10.1111/j.0197-6664.2005.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

To tell or not to tell: Men's disclosure of their HIV‐positive status to their mothers*

Abstract: Disclosing an HIV diagnosis to his mother may be the first step in a man's successful management of his illness, but it may also lead to added stress due to stigmatization. Analyzing data provided by 166 HIV-positive men who lived in the southeastern United States, we found that the most powerful correlate of disclosure was exposure to HIV through homosexual contact. Additionally, those who had AIDS rather than HIV and exhibited more severe symptoms were significantly more likely to have disclosed to their mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…20 Limited evidence suggested that older patients disclosed to fewer family members than their younger counterparts. These findings support previous research by Nokes et al, 63 Shehan et al, 64 Emlet, 57 and Galvan et al 58 in Western settings, and Akani et al 65 and Bouillon et al 29 in resource-limited settings. Second, and more importantly, our results revealed a strong positive association between community support and disclosure to family members.…”
Section: Discussionsupporting
confidence: 89%
“…20 Limited evidence suggested that older patients disclosed to fewer family members than their younger counterparts. These findings support previous research by Nokes et al, 63 Shehan et al, 64 Emlet, 57 and Galvan et al 58 in Western settings, and Akani et al 65 and Bouillon et al 29 in resource-limited settings. Second, and more importantly, our results revealed a strong positive association between community support and disclosure to family members.…”
Section: Discussionsupporting
confidence: 89%
“…Similar research findings showed that men with a higher severity of HIV/AIDS symptoms were more likely to disclose to their mothers after they were unable to conceal the symptoms [37]. Also, highly educated men were found less likely to disclose, which indicated possible higher levels of coping skills and an unwillingness to worry their family members.…”
Section: Experiences Of Disclosure In Mensupporting
confidence: 58%
“…While age was included in their analysis, there was no specific exploration of disclosure practices between younger and older men. Shehan and colleagues 19 studied 166 HIV-seropositive men ages 20-70 and the patterns of disclosure to their mothers. They found older men signifi-cantly less likely than younger men to inform their mother.…”
Section: Stigma and Disclosure In Older Adultsmentioning
confidence: 99%
“…18 By limiting the disclosure of one's HIV status, the possibility of facing stigma and discrimination is thereby controlled. As Shehan and colleagues 19 have suggested, the power of the stigma associated with HIV may override the need for support.…”
Section: Introductionmentioning
confidence: 99%